Penyuluhan Hukum Penyelesaian Perselisihan Dalam Rumah Tangga Melalui Peradilan Adat Aceh Di Kabupaten Nagan Raya - Adella Yuana; Dara Quthni Effida; Ilka Sandela; Nila Trisna; Putri Kemala Sari (AIWADTHU: Jurnal Pengabdian Hukum, 2023)
Introduction: The domestic dispute in Nagan Raya Regency have become a serious problem, as the number of such cases remains high every year. Qanun Number 9 of 2008 converning The Development of Customery and Traditional Life regulates domestic dispute that can be resolved through customary in Nagan Raya Regency takes into consideration the lack of information related to this matterPurposes of Devotion: The purpose of the research providing a legal understanding of dispute resolution in domestic affairs through customary court based on Qanun Number 9 of 2008 concerning The Development of Customery and Traditional LifeMethod of Devotion: The method used id legal counseling to the community of Gampong Bumi Sari, Nagan Raya Regency, through panel discussions where speakers present the material and then continue with question and answer session between the speakers and participantsResults of the Devotion: Qanun Number 9 of 2008 concerning The Development of Customery and Traditional Life regulates dispute within households that can be resolver through Indigenous Judiciary. Its implementation prioritizes peace and balance to achieve a sense of justice for all parties involved. The high number of disputes within household in Nagan Raya Regency is attributed to the lack of awareness many communities, especially in Gampong Bumi Sari, about this law, and the mistrust of the Indigenous Judiciary, which is feared to provide subjective decisions. Preventive efforts to reduce the number of disputes are being carried out, including legal education activities that must be conducted continuously.